Subjective wear trials to evaluate thermal comfort of the foot clothing system including a sweat pad. Issue 8 (3rd August 2017) - Kaplan, Sibel; Aslan, Selcuk
Abstract: Subjective wear trials were conducted to evaluate effects of disposable antibacterial sweat pads on foot thermal comfort. Sweat pads were produced with polypropylene and polylactic acid nonwoven topsheet layers which were treated with different herbal antibacterial materials. Trials were carried out with 10 male subjects under 10 °C and 50% relative humidity simulating sweating during a moderate activity in cold environments. Besides microclimate temperature and relative humidity measurements, subjective thermal (coolness, dampness, and comfort) and other sensations (stickiness, slippiness, etc.) were obtained by five point rating scales. Bending rigidity, friction coefficients, and moisture management properties of the topsheet fabrics and pads were tested. Results show that foot sweat pads enabled drier microclimate, warmer sensations, and higher comfort evaluations. Antibacterial treatments did not affect bending rigidity values of the nonwoven topsheet fabrics, but some applications decreased spreading speed, increased roughness of the pad surfaces, and wetting time values which are not preferable.